Pemakaian metode preview, question, read, summarize, test (PQRST) guna meningkatkan keterampilan membaca pemahaman peserta didik kelas IV sekolah dasar - Budiawan, Muhammad Aldy; Winarni, Retno; Sriyanto, Ismail (Universitas Sebelas Maret, 2021)
Abstract. The study sought to improve the skills of reading comprehension of students from IV B Class at SD Ta’mirul Islam Surakarta 2019/2020. This was conducted by using PQRST methods. Moreover, this research is in the form of Classroom Action Research (CAR) which was run for two cycles. Each cycles has four systematic stages, namely planning, implementing, observing, and reflecting. This study used variety of techniques including interview, observation, tests, and documentation. The validity of the data was tested using data and source triangulation techniques. Data were analyzed using an instrument originally developed by Miles-Huberman. On this research, the average value result of reading comprehension skills is 44.291 with 12,5% of passing percentage in pre-action. In the first cycle, the average acquisition of reading comprehension skills increased to 60.229 with 41,67% of passing percentage. Lastly, in cycle II, the average acquisition of reading comprehension skills increased to 81.062 with 87,5% of passing percentage.. Finding shows that the PQRST methods has been proven to be successful in improving the reading comprehension skills of grade IV B students at SD Ta'mirul Islam Surakarta for the academic year 2019/2020.